Bile salt hydrolase, the member of Ntn-hydrolase family: differential modes of structural and functional transitions during denaturation - Kumar, R. Suresh; Suresh, C. G.; Brannigan, James A.; Dodson, Guy G.; Gaikwad, Sushama M. (IUBMB Life, 2007)
Conformational transitions and functional stability of the bile salt hydrolase (BSH; cholylglycine EC: 3.5.1.24) from Bifidobacterium longum (BlBSH) cloned and expressed in E. coli were studied under thermal, chemical and pH-mediated denaturation conditions using fluorescence and CD spectroscopy. Thermal and Gdn-HCl-mediated denaturation of BlBSH is a multistep process of inactivation and unfolding. The inactivation and unfolding of the enzyme was found to be irreversible. Enzyme activity seems sensitive to even minor conformational changes at the active site. Thermal denaturation as such did not result in any insoluble protein aggregates. However, on treating with 0.25-1 M Gdn-HCl the enzyme showed increasing aggregation at temperatures of 40-55 degrees C indicating more complex structural changes taking place in the presence of chemical denaturants. The enzyme secondary structure was still intact at acidic pH (pH 1-3). The perturbation in the tertiary structure at the acidic pH was detected through freshly formed solvent exposed hydrophobic patches on the enzyme. These changes could be due to the formation of an acid-induced molten globule-like state.
Keywords: Aggregation; Bile salt hydrolase; molten-globule; Unfolding

Bowman-birk protease inhibitor from the seeds of vigna unguiculata forms a highly stable dimeric structure - Rao, K. N.; Suresh, C. G. (Biochimica et Biophysica Acta-Proteins and Proteomics, 2007)
Different protease inhibitors including Bowman-Birk type (BBI) have been reported from the seeds of rigna unguiculata. Protease isoinhibitors of double-headed Bowman-Birk type from the seeds of Vigna unguiculata have been purified and characterized. The BBI from Vigna unguiculata (Vu-BBI) has been found to undergo self-association to form very stable dimers and more complex oligomers, by size-exclusion chromatography and SDS-PAGE in the presence of urea. Many BBIs have been reported to undergo self-association to form homodimers or more complex oligomers in solution. Only one dimeric crystal structure of a BBI (pea-BBI) is reported to date. We report the three-dimensional structure of a Vu-BBI determined at 2.5 A resolution. Although, the inhibitor has a monomer fold similar to that found in other known structures of Bowman-Birk protease inhibitors, its quaternary structure is different from that commonly observed in this family. The structural elements responsible for the stability of monomer molecule and dimeric association are discussed. The Vu-BBI may use dimeric or higher quaternary association to maintain the physiological state and to execute its biological function. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Bowman-Birk protease inhibitor; plant protease inhibitor; protein-protein interaction; Vigna unguiculata